2012
DOI: 10.1163/156856212x629845
|View full text |Cite
|
Sign up to set email alerts
|

Electrosprayed Hydroxyapatite on Polymer Nanofibers to Differentiate Mesenchymal Stem Cells to Osteogenesis

Abstract: Electrospraying of hydroxyapatite (HA) nanoparticles onto the surface of polymer nanofibers provides a potentially novel substrate for the adhesion, proliferation and differentiation of mesenchymal stem cells (MSCs) into bone tissue regeneration. HA nanoparticles (4%) were electrosprayed on the surface of electrospun polycaprolactone (PCL) nanofibers (420 ± 15 nm) for bone tissue engineering. PCL/HA nanofibers were comparatively characterized with PCL/Collagen (275 ± 56 nm) nanofibers by FT-IR analysis to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…FESEM image of MSCs (Figure 8) showed that the standard cell structure on all the samples with more mineral growth on the PCL/SF/HA/MH particles. Cellular function such as adhesion and proliferation showing the preliminary stages of cell-biomaterial interaction, finally leads to differentiation and mineralization [29]. Furthermore, the gradual adhesion of cells in to the nanoparticles was observed and experienced enhanced cell-to-cell interaction with the formation of filapodia structure.…”
Section: Resultsmentioning
confidence: 99%
“…FESEM image of MSCs (Figure 8) showed that the standard cell structure on all the samples with more mineral growth on the PCL/SF/HA/MH particles. Cellular function such as adhesion and proliferation showing the preliminary stages of cell-biomaterial interaction, finally leads to differentiation and mineralization [29]. Furthermore, the gradual adhesion of cells in to the nanoparticles was observed and experienced enhanced cell-to-cell interaction with the formation of filapodia structure.…”
Section: Resultsmentioning
confidence: 99%
“…The natural extracellular matrix (ECM) proteins are in the range of 50-500 nm and with the emergence of nanotechnology it is now possible to devise various polymeric scaffolds at nanoscale levels that mimic the in vivo state. The ideal scaffold should be biocompatible and biodegradable, have large surface area to provide better cell attachment, provide stem cell niches, and possess high porosity to facilitate exchange of nutrients and cell movement (21)(22)(23). Today, there are several different techniques of scaffold fabrication such as electrospinning, phase separation, particulate leaching, fiber bonding, and gas foaming (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Diagrammatic representation of electrospraying and electrospinning system for fabricating PCL/HA nanofibers[36].…”
mentioning
confidence: 99%